1990
DOI: 10.1557/jmr.1990.2698
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal crystallization kinetics ofm-ZrO2andt-ZrO2

Abstract: The isothermal nucleation and crystallization kinetics of hydrothermally prepared monoclinic and tetragonal ZrO2 have been determined at various pH conditions. It is shown that monoclinic ZrO2 precipitates at low pH whereas at high pH tetragonal ZrO2 crystallizes from an amorphous zirconium (hydrous) oxide, Zr(OH)xOy, precursor. At intermediate pH conditions mixtures of the polymorphs are formed suggestive of kinetically competing particle formation mechanisms. The data are explained by the proposed existence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 34 publications
5
78
3
Order By: Relevance
“…[27,28] Metastable t-ZrO 2 can be obtained by the thermal treatment of suitable starting materials (such as zirconium salts, zirconium alkoxides, or zirconium hydroxide). [27±30] In the case of gel-derived zirconia, particle size, [31] structural similarities between amorphous gels and crystalline phases, [32] and impurities [33] all have an influence on the existence of metastable phase t-ZrO 2 . The crystalline zirconia size of 30 nm or less is now believed to stabilize the tetragonal form at room temperature due to the contribution of surface energy [34] and size effects.…”
Section: Resultsmentioning
confidence: 99%
“…[27,28] Metastable t-ZrO 2 can be obtained by the thermal treatment of suitable starting materials (such as zirconium salts, zirconium alkoxides, or zirconium hydroxide). [27±30] In the case of gel-derived zirconia, particle size, [31] structural similarities between amorphous gels and crystalline phases, [32] and impurities [33] all have an influence on the existence of metastable phase t-ZrO 2 . The crystalline zirconia size of 30 nm or less is now believed to stabilize the tetragonal form at room temperature due to the contribution of surface energy [34] and size effects.…”
Section: Resultsmentioning
confidence: 99%
“…This process yields fine crystalline or amorphous zirconium oxide. 38 A relationship between the crystal structure and the pH of the precipitation of hydrous zirconia was reported. 39 It was shown that the pH of the solution from which the gel precipitates determines the crystal phase of the calcined zirconia.…”
Section: Precipitation Of Hydrous Zirconiamentioning
confidence: 99%
“…Under strongly alkaline conditions caused by NaOH, only the tetragonal phase was formed while acidic conditions led to the monoclinic phase. Hydrothermal treatment of zirconyl nitrate and zirconyl chloride solutions showed the same dependence of phase and pH [72][73][74]. Differences in the solubility of hydrous zirconia at different pH was put forth to explain the formation of different crystallite phases.…”
Section: Effect Of Phmentioning
confidence: 99%